Effects of Irradiation of CO2 Laser on the Regeneration of Periodontal Tissue - Kamoi, Kyuichi; Agatsuma, Mizuho; Kamoi, Hisahiro; Sato, Soh (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 1999)
Local irradiation of the superficial layer of periodontal tissue using a CO2 laser has received much attention as a means of forming a site where periodontal tissue may be regenerated. In this study, we examined the feasibility of using a CO2 laser to treat the surface of the dental root. Morphological changes in the irradiated surface of dentin and the depth of irradiation to the dentin were examined using scanning electron microscopy (SEM) and confocal laser scanning microscopy. To examine the regeneration of periodontal tissue after CO2 laser irradiation, experimentally induced periodontitis in dogs was irradiated with CO2 laser treatments. The newly adhered and regenerated bone tissue was then examined histopathologically. The following results were obtained: 1) The amount of smear layers removed from the surface of the dentin and the increase in the degree of jaw opening were dependent on the energy density (0.6J/cm2 0J/cm2) of the laser. When the energy density was 1.2 J/cm2 more, the intertubular dentin resolidfed. 2) The depth of irradiation to the surface of the dentin increased when the energy density of the laser was increased. 3) An energy density of 1.0J/cm2 was found to be the most suitable level for dental root treatments. 4) A significant amount of regeneration, i. e., new adhesion and new bone growth, was observed in periodontitis cases that received postoperative laser irradiation treatments with an energy density of 1.0J/cm2, as compared with cases that did not receive iradiation treatments. J. Japan. Soc. Periodont., 41: 264-276, 1999.